A disulfide bridge in the calcium binding site of a polyester hydrolase increases its thermal stability and activity against polyethylene terephthalate. Issue 5 (1st April 2016) - Then, Johannes; Wei, Ren; Oeser, Thorsten; Gerdts, André; Schmidt, Juliane; Barth, Markus; Zimmermann, Wolfgang
Abstract : Elevated reaction temperatures are crucial for the efficient enzymatic degradation of polyethylene terephthalate (PET). A disulfide bridge was introduced to the polyester hydrolase TfCut2 to substitute its calcium binding site. The melting point of the resulting variant increased to 94.7 °C (wild‐type TfCut2: 69.8 °C) and its half‐inactivation temperature to 84.6 °C (TfCut2: 67.3 °C). The variant D204C‐E253C‐D174R obtained by introducing further mutations at vicinal residues showed a temperature optimum between 75 and 80 °C compared to 65 and 70 °C of the wild‐type enzyme. The variant caused a weight loss of PET films of 25.0 ± 0.8% (TfCut2: 0.3 ± 0.1%) at 70 °C after a reaction time of 48 h. The results demonstrate that a highly efficient and calcium‐independent thermostable polyester hydrolase can be obtained by replacing its calcium binding site with a disulfide bridge. Abstract : Elevated reaction temperatures are crucial for the efficient enzymatic degradation of polyethylene terephthalate (PET). A disulfide bridge substituting the calcium binding site of the polyester hydrolase TfCut2 caused a remarkable melting point increase of 24.9 °C. As a consequence, enzymatic PET hydrolysis could be observed at 70 °C, resulting in a weight loss of PET films of 25.0 ± 0.8% after a reaction time of 48 h.